Unicompartmental knee arthroplasty suitability: a retrospective study at Chris Hani Baragwanath Academic Hospital - Thwala, Edmund Nkhensani (My University, 2020)
Background: Having noticed the limited practice of unicompartmental knee arthroplasty (UKA) at Chris Hani Baragwanath Academic Hospital (CHBAH), the urge to understand principles involved in the surgery and practice in general, arose. With review of literature, we understood the course that the practice of UKA had taken in the past two decades, where in the early nineties it was popular, but due to high revision rates, it saw a decline. Revivers of UKA then established the need to give attention to patient selection and established criteria deemed essential to prevent the high failure rates. Even then only 6% of patients are expected to be suitable for UKA. The large number of patients seen at CHBAH was the basis of our interest to establish if our patients met the criteria for UKA. This would also give an insight into the pattern of knee affectation by Osteoarthritis in our local population. Methods: Following acquisition of both the University of the Witwatersrand Human Research Ethics (HREC-Medical) and CHBAH Institutional Ethics approval for our study, we conducted a retrospective review of patient records for a period of three years, i.e. 2015 to 2017. A data collection sheet was used to collect the data highlighting the essential criteria for UKA in each patient and also sampling information on the pattern of Osteoarthritis at CHBAH. Results: Following the application of exclusion criteria, a total of 202 patients were left for evaluation of suitability for UKA and to assess the pattern of manifestation of Osteoarthritis (OA) of the knee at CHBAH. The bio-demographic distribution of the study population showed a 1:1.3 male to female ratio with the total number of patients being 2.7 times more than the recommended number to meet the power analysis as calculated in the Methodology section. The overall findings showed advanced stages of tricompartmental and bicompartmental OA, with women showing a more advanced disease, even in the few cases of unicompartmental OA. None of our patients met criteria for UKA when the traditional criteria were used. Conclusion: The practice of UKA remains a popular topic with high levels of scrutiny. Our study found that all our patients were not suitable for UKA after the application of the traditional criteria. Furthermore, the unsuitability for UKA was predominantly due to high body mass index (BMI), advanced age and severe forms of OA. With improvements of biomaterials and surgical techniques, higher levels of BMI and advanced age are now acceptable for UKA with new criteria dedicated to the use of these new implants. We remain confident that more patients will be suitable for UKA with the new criteria.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Medicine to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020